Effects of Antimicrobial or Probiotic Treatments on Growth Performance of 13- to 56-lb Nursery Pigs - D. Shawk; B. J. Feehan; O. L. Harrison; J. C. Woodworth; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. M. DeRouchey; N. E. Ward; A. B. Clark (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 612 nursery pigs (21-d of age; Line 241 × 600; DNA, Columbus, NE) were used in two 44-d experiments to determine effects of antibiotic or different probiotic products on nursery pig performance and fecal consistency. In Experiment 1, 297 pigs (initially 12.8 lb) were used with 6 replications per treatment and 5 or 6 pigs per pen. In Experiment 2, 315 pigs (initially 13.3 lb) were used with 7 replications per treatment and 5 pigs per pen. In both experiments, pens were randomly allotted to 1 of 9 dietary treatments in a randomized complete block design. The nine treatment diets included a control diet, or the control diet with either carbadox (Mecadox-2.5 Phibro Animal Health, Teaneck, NJ) at 50 g/ton, BioPlus 2B (Chr. Hansen USA, Inc., Milwaukee, WI) with an inclusion rate of 0.05%, or 1 of 6 DSM Probiotic products (DSM Nutritional Products, Inc., Parsippany, NJ) with an inclusion rate of 0.20%. For Experiment 1, pigs fed the diet containing carbadox had increased (P<0.05) ADG compared to pigs fed the control diet or diets containing DSM Probiotic 1, 2, 3, or 6, with the other probiotic treatments intermediate. Pigs fed the diet with carbadox had greater (P<0.05) ADFI compared to those fed the control or diets containing DSM Probiotic 1, 2, or 3, with the other probiotic treatments intermediate. Feed efficiency was not affected by treatment. For fecal consistency, there was no evidence to indicate a treatment effect (P>0.05) or treatment × day interaction (P = 0.951). For Experiment 2, pigs fed carbadox had greater (P<0.05) ADG than all other treatments. Pigs fed BioPlus 2B had greater (P<0.05) ADG compared to those fed the diet containing DSM Probiotic 3, with the control and all other probiotic treatments intermediate. Pigs fed carbadox had increased (P<0.05) ADFI compared to the control and DSM Probiotics, with BioPlus 2B intermediate. There was no evidence of difference to indicate that dietary treatment influenced F/G nor to indicate a treatment effect for fecal consistency. In summary, pigs fed diets containing carbadox consistently had increased ADG and ADFI compared to pigs fed any of the other dietary treatments. There was no evidence the probiotics improved performance based on these results; however, the DSM probiotic 4 had the highest numerical ADG of all the DSM products relative to the nonmedicated control diet in both experiments.
Keywords: antibiotic; fecal consistency; growth; nursery pig; probiotic